Multi Akad dalam Aplikasi Mobile Banking Bank Syariah Indonesia Perspektif Fiqh Muamalah - Maarif, Muhamat Nur; Munir, Sirajul (Sharia Faculty Islamic Economic Law Study Department, 2022)
The ease of service provided by Islamic banking has become increasingly advanced. One of them is a mobile banking service owned by Bank Syariah Indonesia under the name BSI Mobile, where customers will get various conveniences of service facilities with just one application downloaded using Play Strore for Android and the App store of IOS (Iphone Operating System) users. Mobile services and various contracts that have innovated are the basis for the author to examine the validity of contracts carried out by customers, where the purpose of this study is to examine hybrid contracts contained in BSI Mobile. The author uses an empirical juridical approach, combining primary data and data in the field so that the suitability of theory and practice at Bank Syariah Indonesia is found. Based on the results of this study, there are new products in Islamic Banking contained in BSI Mobile. Most of BSI Mobile products actually contain several contracts so it is necessary to apply sharia principles, especially in terms of their conformity with contracts.